New Noncoding Base Pair Mutation at the Identical Locus as the Original NCMD/MCDR1 in a Mexican Family, Suggesting a Mutational Hotspot. (January 2023) - Small, Kent W.; Van de Sompele, Stijn; Avetisjan, Jessica; Udar, Nitin; Agemy, Steven; De Baere, Elfride; Shaya, Fadi S.
Purpose: To clinically and molecularly study a newly found family with North Carolina macular dystrophy (NCMD/MCDR1) from Mexico. Methods: This retrospective study comprised 6 members of a 3-generation Mexican family with NCMD. Clinical ophthalmic examinations, including fundus imaging, spectral-domain optical coherence tomography, electroretinography, and electrooculography, were performed. Genotyping with polymorphic markers in the MCDR1 region was performed to determine haplotypes. Whole-genome sequencing (WGS) was performed followed by variant filtering and copy number variant analysis. Results: Four subjects from 3 generations were found to have macular abnormalities. The proband presented with lifelong bilateral vision impairment with bilaterally symmetric vitelliform Best disease-like appearing macular lesions. Her 2 children had bilateral large macular coloboma-like malformations, consistent with autosomal dominant NCMD. The 80-year-old mother of the proband had drusen-like lesions consistent with grade 1 NCMD. WGS and subsequent Sanger sequencing found a point mutation at chr6:99593030G>C (hg38) in the noncoding region of the DNase I site thought to be a regulatory element of the retinal transcription factor gene PRDM13 . This mutation is the identical site/nucleotide as in the original NCMD family (#765) but is a guanine to cytosine change rather than a guanine to thymine mutation, as found in the original NCMD family. Conclusions: We report a new noncoding mutation at the same locus (chr6:99593030G>C) involving the same DNase I site regulating the retinal transcription factor gene PRDM13. This suggests that this site, chr6:99593030, is a mutational hotspot.